Non-oriented films, laminates, and packages
Patent Information
- Application Number
- JP2023576940
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-01-25
AI Technical Summary
【0017】 本発明の無延伸フィルムは、該無延伸フィルムを構成するシーラント層に、所定の割合で特定のプロピレン系重合体、1-ブテン·α-オレフィン共重合体、およびプロピレン·α-オレフィン共重合体を含む樹脂組成物を用いることにより、前記無延伸フィルムを用いた積層体は、低温ヒートシール性およびヒートシール強度がバランスよく優れる。また、本発明の無延伸フィルムを用いた積層体は、剥離外観に優れ、耐ブロッキング性にも優れる傾向にある。
Smart Images

Figure 0007642105000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-oriented film, a laminate, and a package comprising a sealant layer and a substrate layer. [Background technology]
[0002] Heat-seal packaging films are made up of multiple layers of film. In the field of heat-seal packaging films, for example, for packages that require high sealing strength for liquids or retort packaging, there is a tendency for non-oriented films to be used in the multilayer film. In addition, polypropylene (PP) films and polyethylene (PE) films are widely used as heat-seal packaging films, and among these, mono-material films such as PP mono-material packaging and PE mono-material packaging are considered important from the perspective of recycling needs.
[0003] Resin compositions in which propylene-based copolymers are blended with ethylene-based copolymers and films using only ethylene-based copolymers are widely used as sealant films for packaging applications. For example, Patent Documents 1 and 2 describe laminates with excellent low-temperature heat sealability, which include sealant films containing polypropylene resin, propylene-α-olefin copolymer, and 1-butene-α-olefin copolymer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 027885 [Patent Document 2] Patent Publication No. 2021-070250 Summary of the Invention [Problem to be solved by the invention]
[0005] Normally, in mono-material packaging using an olefin material (e.g., PP), the heat resistance of the substrate (e.g., PP) is reduced, so that the sealant layer of the non-stretched film needs to have a sealability (low-temperature sealability) at a temperature at which the substrate does not thermally shrink. However, when the films described in Patent Documents 1 and 2 are used as the non-stretched film, further improvement is required in terms of the balance between the low-temperature heat sealability and the heat seal strength of the resulting laminate.
[0006] The present invention has been made in view of the above, and an object of the present invention is to provide a non-oriented film which can constitute a laminate having a well-balanced excellent low-temperature heat sealability and heat seal strength. [Means for solving the problem]
[0007] The present invention relates to, for example, the following [1] to
[10] . [1] 20 to 75 mass% of a propylene-based polymer (A), 20 to 75 mass% of a 1-butene / α-olefin copolymer (B), Propylene-α-olefin copolymer (C) 5 to 40 mass % a sealant layer made of a resin composition comprising the above (wherein the total of the propylene-based polymer (A), the copolymer (B) and the copolymer (C) is 100 mass %); and Base material layer 2. An unstretched film having: The content of the copolymer (B) is equal to or greater than the content of the copolymer (C); The total content of the copolymer (B) and the copolymer (C) is 25 to 80 mass %, The propylene polymer (A) has a melting point (Tm) measured by differential scanning calorimetry (DSC) of 120° C. or more and 170° C. or less; The copolymer (B) has a Tm measured by DSC of less than 120° C. or no Tm is observed by DSC, and contains 51 to 99 mol % of structural units derived from 1-butene and 1 to 49 mol % of structural units derived from an α-olefin having 2 to 3 carbon atoms or 5 to 20 carbon atoms (with the proviso that the total of the structural units derived from 1-butene and the structural units derived from the α-olefin is 100 mol %); The copolymer (C) has a Tm measured by DSC of less than 120° C. or no Tm is observed by DSC, and contains 51 to 95 mol % of structural units derived from propylene and 5 to 49 mol % of structural units derived from an α-olefin having 2 or 4 to 20 carbon atoms (however, the total of the structural units derived from propylene and the structural units derived from the α-olefin is 100 mol %). Unstretched film.
[0008] [2] The non-oriented film according to [1], wherein the copolymer (C) contains one or more propylene-α-olefin copolymers selected from the group consisting of propylene-ethylene copolymers (C1) and propylene-1-butene copolymers (C2).
[0009] [3] The non-oriented film according to [1] or [2], wherein the base layer contains the propylene-based polymer (A) (which may be the same as or different from the propylene-based polymer (A) contained in the sealant layer).
[0010] [4] The unstretched film according to any one of [1] to [3], wherein the sealant layer has a thickness of 3 to 30 μm, and the base layer has a thickness of 10 to 100 μm.
[0011] [5] A laminate comprising the unstretched film according to any one of [1] to [4] and a stretched film.
[0012] [6] The laminate according to [5], wherein the stretched film is a film selected from the group consisting of a stretched polyethylene terephthalate film and a stretched polypropylene film.
[0013] [7] The laminate according to [5] or [6], wherein the stretched film has a thickness of 10 to 50 μm.
[0014] [8] The maximum heat seal strength in the temperature range of 70°C to 120°C is 8N / 15mm or more. The maximum heat seal strength in the temperature range of 70°C to 200°C is 15N / 15mm or more, The laminate according to any one of [5] to [7], wherein, in a heat seal strength measurement in a temperature range of 70°C or higher and 200°C or lower, when the heat seal strength is 30 N / 15 mm or higher, the peeling morphology of the heat seal portion is edge tearing.
[0015] [9] Further comprising at least one functional layer selected from a printing layer, a barrier layer, and an embossed layer; The laminate according to any one of [5] to [8], wherein the functional layer is adjacent to or in contact with at least one layer or film selected from the sealant layer, the base layer, and the stretched film via an adhesive layer.
[0016]
[10] A packaging material formed from the laminate according to any one of [5] to [9]. Effect of the Invention
[0017] The non-stretched film of the present invention uses a resin composition containing a specific propylene-based polymer, a 1-butene / α-olefin copolymer, and a propylene / α-olefin copolymer in a predetermined ratio in the sealant layer constituting the non-stretched film, and thus a laminate using the non-stretched film has a well-balanced and excellent low-temperature heat sealability and heat seal strength. In addition, the laminate using the non-stretched film of the present invention tends to have excellent peel appearance and blocking resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [Non-oriented film] The non-stretched film of the present invention has a sealant layer and a substrate layer. That is, the non-stretched film of the present invention has a structure in which the sealant layer and the substrate layer are laminated. The sealant layer is a layer that imparts thermal adhesion to a laminate having the non-stretched film and the stretched film, and the substrate layer is a layer that supports the sealant layer.
[0019] <Sealant layer> The sealant layer is made of a resin composition containing the following components (A) to (C) in a given ratio: (A) A propylene-based polymer (hereinafter also referred to as "(co)polymer (A)") having a melting point (Tm) measured by differential scanning calorimetry (DSC) of 120°C or higher and 170°C or lower. (B) A 1-butene-α-olefin copolymer (hereinafter also referred to as "copolymer (B)") which has a melting point of less than 120°C as measured by DSC or no melting point is observed by DSC, and contains 51 to 99 mol % of structural units derived from 1-butene and 1 to 49 mol % of structural units derived from an α-olefin having 2 to 3 carbon atoms or 5 to 20 carbon atoms (however, the total of the structural units derived from 1-butene and the structural units derived from an α-olefin having 2 to 3 carbon atoms or 5 to 20 carbon atoms is 100 mol %). (C) A propylene-α-olefin copolymer having a melting point of less than 120°C or no melting point observed by DSC, containing 51 to 95 mol % of structural units derived from propylene and 5 to 49 mol % of structural units derived from an α-olefin having 2 or 4 to 20 carbon atoms (the total of the structural units derived from propylene and the structural units derived from an α-olefin having 2 or 4 to 20 carbon atoms is 100 mol %) (hereinafter also referred to as "copolymer (C)").
[0020] <Propylene-based polymer (A)> Examples of the propylene polymer (A) include a homopolymer of propylene, a random copolymer of propylene and an α-olefin having 2 or 4 to 20 carbon atoms, and a block copolymer of propylene and an α-olefin having 2 or 4 to 20 carbon atoms, and preferably a homopolymer of propylene or a random copolymer of propylene and an α-olefin having 2 or 4 to 20 carbon atoms. The (co)polymer (A) may be one type of (co)polymer or two or more types of (co)polymers.
[0021] In the resin composition constituting the sealant layer in the present invention, it is particularly preferable to use a homopolymer of propylene from the viewpoint of imparting heat resistance and rigidity to the sealant layer, while it is particularly preferable to use a random copolymer of propylene and an α-olefin having 2 carbon atoms or 4 to 20 carbon atoms from the viewpoint of imparting flexibility and transparency to the sealant layer.
[0022] Examples of the α-olefin having 2 carbon atoms or 4 to 20 carbon atoms to be copolymerized with propylene include ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. The α-olefins may be used alone or in combination of two or more.
[0023] When a random copolymer of propylene and an α-olefin having 2 carbon atoms or 4 to 20 carbon atoms is used as the (co)polymer (A), the (co)polymer (A) preferably contains 91 to 99.9 mol %, more preferably 92 to 99.8 mol %, and even more preferably 93 to 99.7 mol % of structural units derived from propylene and a random copolymer of propylene and an α-olefin having 2 carbon atoms or 4 to 20 carbon atoms. Composition The unit is contained in an amount of 0.1 to 9 mol %, preferably 0.2 to 8 mol %, and more preferably 0.3 to 7 mol % (however, the total of the propylene-derived structural units and the α-olefin-derived structural units is 100 mol %).
[0024] The (co)polymer (A) has a melting point (Tm) measured by differential scanning calorimetry (DSC) of 120° C. or more and 170° C. or less, preferably 125° C. or more and 165° C. or less. By using the (co)polymer (A) having a melting point within the above range, the moldability of the sealant layer is improved, and the sealant layer can be provided with heat resistance and transparency. Furthermore, the heat of fusion (ΔH) obtained simultaneously with the melting point by DSC is preferably 50 mJ / mg or more.
[0025] The melting point (Tm) of the (co)polymer (A) was measured by measuring the temperature of the apex of the crystal melting peak when a sample of about 5 mg was heated to 200° C. in a nitrogen atmosphere (20 mL / min) using a differential scanning calorimeter (e.g., DSC Pyris1 or DSC7 manufactured by PerkinElmer) and held for 10 minutes, then cooled to 30° C. at 10° C. / min, held for 5 minutes, and then heated to 200° C. at 10° C. / min. (Total) Polymer (A) The melting point (Tm) of the sample is taken as the melting point (Tm) of the sample. If multiple peaks are detected, the peak detected at the highest temperature is used.
[0026] The melt flow rate (MFR) of the (co)polymer (A) is preferably 0.01 to 40 g / 10 min, more preferably 0.1 to 10 g / 10 min, as measured at 230° C. and under a load of 2.16 kg in accordance with ASTM D1238. By using the (co)polymer (A) having an MFR within the above range, the fluidity of the resin composition constituting the sealant layer is improved, and even a relatively large sheet can be easily molded.
[0027] The (co)polymer (A) can be produced by polymerizing monomers in the presence of a known catalyst such as a Ziegler-Natta catalyst, a metallocene catalyst, etc., by a known polymerization method such as a gas phase method, a bulk method, a slurry method, etc. As an example of a method for adjusting the melting point to 120°C or more and 170°C or less, there is a method of controlling the polymerization conditions such as the monomer feed amount to control the comonomer content to less than 20 mol% in the case of polymerization with a Ziegler-Natta catalyst, and to less than 10 mol% in the case of polymerization with a metallocene catalyst, and by this method, a polymer having a target melting point can be obtained.
[0028] <1-butene / α-olefin copolymer (B)> The 1-butene-α-olefin copolymer (B) may be, for example, a copolymer of 1-butene and an α-olefin having 2 to 3 carbon atoms or 5 to 20 carbon atoms. The copolymer (B) may be one type of copolymer or two or more types of copolymers. In general, the use of 1-butene·α-olefin copolymers improves the low-temperature sealability and blocking resistance of laminates.
[0029] Examples of α-olefins having 2 to 3 carbon atoms or 5 to 20 carbon atoms that are copolymerized with 1-butene include ethylene, propylene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and among these α-olefins, ethylene, propylene, and 1-pentene are preferred, ethylene and propylene are more preferred, and propylene is even more preferred. The α-olefins may be used alone or in combination of two or more.
[0030] The copolymer (B) contains 51 to 99 mol %, preferably 60 to 97 mol %, and more preferably 70 to 95 mol % of structural units derived from 1-butene, and 1 to 49 mol %, preferably 3 to 40 mol %, and more preferably 5 to 30 mol % of structural units derived from an α-olefin having 2 to 3 carbon atoms or 5 to 20 carbon atoms (however, the total of the structural units derived from 1-butene and the structural units derived from the α-olefin is 100 mol %). By setting the temperature within the above range, the handling property is excellent and heat sealing is easy even at a relatively low temperature.
[0031] The copolymer (B) has a melting point measured by DSC of less than 120° C. or no melting point is observed by DSC, and preferably has a melting point of 50° C. to 115° C., more preferably 60° C. to 110° C., and even more preferably 65° C. to 110° C. By using the copolymer (B) having a melting point within the above range, heat sealing is easy even at a relatively low temperature and good surface properties are obtained.
[0032] The melting point (Tm) of the copolymer (B) was measured by using a differential scanning calorimeter (e.g., DSC manufactured by Seiko Instruments Inc.) by filling an aluminum pan with about 10 mg of a sample, heating it to 200°C at 100°C / min, holding it there for 5 minutes, cooling it to -100°C at 10°C / min, and then heating it to 200°C at 10°C / min, and measuring the temperature at the top of the crystal melting peak. Total Polymer (B)The melting point (Tm) of the sample is taken as the melting point (Tm) of the sample. If multiple peaks are detected, the peak detected at the highest temperature is used.
[0033] The melt flow rate (MFR) of the copolymer (B) measured according to ASTM D1238 at 230°C and a load of 2.16 kg is preferably 0.1 to 30 g / 10 min, more preferably 0.5 to 20 g / 10 min, and even more preferably 1.0 to 10 g / 10 min. Furthermore, in the copolymer (B) having an MFR at 230°C in the above range, the melt flow rate (MFR) measured according to ASTM D1238 at 190°C and a load of 2.16 kg is preferably 0.1 to 30 g / 10 min, more preferably 0.5 to 20 g / 10 min, and even more preferably 1.0 to 10 g / 10 min. By using the copolymer (B) having an MFR in the above range, the fluidity of the resin composition constituting the sealant layer is improved, and even a relatively large sheet can be easily molded.
[0034] The copolymer (B) can be produced by polymerizing monomers in the presence of a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a known polymerization method such as a gas phase method, a bulk method, a slurry method, etc. As an example of a method for making the melting point less than 120°C, there is a method of controlling the polymerization conditions such as the monomer feed amount, and controlling the comonomer content to 20 mol% or more and 50 mol% or less when polymerizing with a Ziegler-Natta catalyst, and controlling the comonomer content to 10 mol% or more and 50 mol% or less when polymerizing with a metallocene catalyst, and by this method, a copolymer having a target melting point can be obtained.
[0035] <Propylene-α-olefin copolymer (C)> The propylene-α-olefin copolymer (C) may be, for example, a copolymer of propylene and an α-olefin having 2 carbon atoms or 4 to 20 carbon atoms. The copolymer (C) may be one type of copolymer or two or more types of copolymers. Generally, the use of propylene / α-olefin copolymers is inexpensive and improves heat seal strength, but low-temperature sealability and blocking resistance are insufficient. Therefore, by combining them with the relatively expensive 1-butene / α-olefin copolymers, it becomes easier to achieve both excellent heat seal strength, low-temperature sealability and blocking resistance of the laminate, as well as various physical properties and reduced manufacturing costs.
[0036] Examples of the α-olefin having 2 carbon atoms or 4 to 20 carbon atoms to be copolymerized with propylene include ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. The α-olefins may be used alone or in combination of two or more.
[0037] Specific examples of the copolymer (C) selected from the above α-olefins include a propylene-ethylene copolymer (C1), a propylene-1-butene copolymer (C2), a propylene-1-pentene copolymer, a propylene-1-hexene copolymer, a propylene-3-methyl-1-butene random copolymer, and a propylene-4-methyl-1-pentene random copolymer.
[0038] The copolymer (C) preferably contains one or more propylene-α-olefin copolymers selected from the group consisting of propylene-ethylene copolymers (C1) and propylene-1-butene copolymers (C2), and more preferably contains propylene-1-butene copolymers (C2) since they tend to have excellent blocking power.
[0039] The copolymer (C) contains 51 to 99 mol %, preferably 60 to 95 mol %, and more preferably 70 to 90 mol % of structural units derived from propylene, and 1 to 49 mol %, preferably 5 to 40 mol %, and more preferably 10 to 30 mol % of structural units derived from an α-olefin having 2 or 4 to 20 carbon atoms (however, the total of the structural units derived from propylene and the structural units derived from the α-olefin is 100 mol %). By setting the temperature within the above range, heat sealing is easy even at a relatively low temperature, and good surface properties are achieved.
[0040] The copolymer (C) has a melting point of less than 120°C as measured by DSC or no melting point is observed by DSC, and preferably has a melting point of 50°C or more and 110°C or less, more preferably 60°C or more and 100°C or less, and even more preferably 65°C or more and 95°C or less. By using the copolymer (C) having a melting point within the above range, heat sealing is easy even at a relatively low temperature and good surface properties are obtained. The melting point (Tm) of the copolymer (C) can be determined, for example, by the same method as the method for measuring the melting point of the copolymer (B) described above.
[0041] The melt flow rate (MFR) of the copolymer (C) measured according to ASTM D1238 at 230°C and under a load of 2.16 kg is preferably 0.1 to 30 g / 10 min, more preferably 0.5 to 20 g / 10 min, and even more preferably 1.0 to 10 g / 10 min. Furthermore, in the copolymer (C) whose MFR at 230°C is within the above range, the melt flow rate (MFR) measured according to ASTM D1238 at 190°C and under a load of 2.16 kg is preferably 0.1 to 30 g / 10 min, more preferably 0.5 to 20 g / 10 min, and even more preferably 1.0 to 10 g / 10 min. By using the copolymer (C) whose MFR at the above two temperatures is within the above range, the flowability of the resin composition constituting the sealant layer is improved, and even a relatively large sheet can be easily molded.
[0042] The copolymer (C) can be produced by polymerizing monomers in the presence of a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a known polymerization method such as a gas phase method, a bulk method, a slurry method, etc. As an example of a method for making the melting point less than 120°C, a method of controlling the polymerization conditions such as the monomer feed amount, etc., and controlling the comonomer content to 20 mol% or more and 50 mol% or less when polymerizing with a Ziegler-Natta catalyst, or to 10 mol% or more and 50 mol% or less when polymerizing with a metallocene catalyst, can be mentioned, and by this method, a copolymer having a target melting point can be obtained.
[0043] <Resin composition constituting sealant layer> The resin composition constituting the sealant layer in the present invention contains a (co)polymer (A), a copolymer (B), and a copolymer (C). The content of each component is 20 to 75% by mass, preferably 23 to 70% by mass, and more preferably 25 to 65% by mass of the (co)polymer (A), 20 to 75% by mass, preferably 23 to 70% by mass, and more preferably 25 to 65% by mass of the copolymer (B), and 5 to 40% by mass, preferably 7 to 37% by mass, and more preferably 10 to 35% by mass of the copolymer (C) (however, the total content of the (co)polymer (A), the copolymer (B), and the copolymer (C) is 100% by mass).
[0044] Here, it is more preferable that the content of the (co)polymer (A) is equal to or greater than the content of the copolymer (B) while the content of the (co)polymer (A) is within the above-mentioned range and the content of the copolymer (B) is equal to or greater than the content of the copolymer (B). If the content of the (co)polymer (A) is equal to or greater than the content of the copolymer (B), the peeling mode of the heat-sealed portion of the laminate tends to be edge cutting, which will be described later.
[0045] The content of the copolymer (B) is equal to or greater than the content of the copolymer (C), and the total content of the copolymers (B) and (C) is 25 to 80 mass%, preferably 30 to 77 mass%, and more preferably 35 to 75 mass%. When the content of each component contained in the resin composition is within the above range, a laminate having excellent low-temperature sealability and sufficient heat seal strength can be produced.
[0046] The sealant layer may contain additives, such as resins other than the (co)polymers (A) to (C), tackifiers, weather stabilizers, heat stabilizers, antistatic agents, slip agents, antiblocking agents, lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, and antioxidants, as necessary, within the scope of the object of the present invention. The sealant layer may be made up of one layer or multiple layers.
[0047] The (co)polymers (A) to (C) used in the resin composition constituting the sealant layer and the (co)polymer used in the resin composition constituting the substrate layer described below (hereinafter collectively referred to as "(co)polymer used in the present invention") may each contain at least one or more types of biomass-derived monomers (biomass-derived propylene, biomass-derived ethylene, biomass-derived α-olefins having 4 to 20 carbon atoms). The same type of monomer constituting the polymer may be only biomass-derived monomers, may be only fossil fuel-derived monomers, or may contain both biomass-derived monomers and fossil fuel-derived monomers.
[0048] ≪Base material layer≫ The resin composition constituting the base layer is preferably polypropylene. Examples of the polypropylene include homopolymers of propylene and copolymers having propylene as a main monomer. In the case of copolymers, they may be random copolymers or block copolymers. Examples of monomers copolymerizable with propylene include α-olefins having 2 or 4 to 20 carbon atoms, diene compounds, and the like. The polypropylene is a propylene-derived Composition The unit is 85 to 100 mol %, preferably 90 to 99.5 mol %, and is not derived from other monomers. CompositionThe unit is contained in an amount of 0 to 15 mol %, preferably 0.5 to 10 mol % (however, the unit derived from propylene and the unit derived from other monomers are not included). Composition The sum of the units is 100 mol %.
[0049] Examples of the α-olefin having 2 carbon atoms or 4 to 20 carbon atoms to be copolymerized with propylene include ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, etc. The α-olefins may be used alone or in combination of two or more.
[0050] The melt flow rate (MFR) of the polypropylene is measured in accordance with ASTM D1238 under conditions of 230°C and a load of 2.16 kg and is preferably 0.01 to 400 g / 10 min, more preferably 0.1 to 100 g / 10 min, and the melting point (Tm) is preferably 115 to 175°C, more preferably 120 to 170°C.
[0051] Specifically, the polypropylene is a propylene copolymer. Single weight Examples of the polypropylene random copolymers include propylene-ethylene random copolymers, propylene-1-butene random copolymers, propylene-1-butene-ethylene random copolymers, propylene-1-hexene random copolymers, propylene-3-methyl-1-butene random copolymers, and propylene-4-methyl-1-pentene random copolymers. The polypropylenes may be used alone or in combination of two or more.
[0052] The polypropylene can be produced by polymerizing monomers in the presence of a known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst by a known polymerization method such as a gas phase method, a bulk method, or a slurry method. The polypropylene contained in the resin composition constituting the base layer is preferably the propylene-based polymer (A) contained in the resin composition constituting the sealant layer described above. When the resin composition constituting the base layer contains a (co)polymer (A), the type of the (co)polymer (A) may be the same as or different from the (co)polymer (A) used in the resin composition constituting the sealant layer.
[0053] The base layer may contain additives such as resins other than polypropylene, tackifiers, weather stabilizers, heat stabilizers, antistatic agents, slip agents, antiblocking agents, lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, and antioxidants, as long as the object of the present invention is not impaired. The substrate layer may be made up of one layer or multiple layers.
[0054] <How to make non-oriented film> The non-stretched film of the present invention can be obtained by laminating a sealant layer and a substrate layer. For example, the non-stretched film can be produced by co-extrusion molding using two extruders connected to a T-die, supplying the resin composition constituting the sealant layer and the resin composition constituting the substrate layer to each extruder.
[0055] The thickness of the sealant layer is usually 3 to 30 μm, preferably 5 to 25 μm, and the thickness of the base layer is usually 10 to 100 μm, preferably 20 to 75 μm. When there are a plurality of sealant layers and base layers, Each layer The total thickness of the non-stretched film of the present invention is preferably within the above range.
[0056] <Laminate> The laminate of the present invention has the above-mentioned non-stretched film and stretched film. The embodiment of the laminate includes, but is not limited to, structures such as non-stretched film / stretched film and non-stretched film / stretched film / stretched film. For example, when a plurality of non-stretched films of the present invention are used, one type may be used alone or two or more types may be used. In addition, an adhesive layer may be provided between the non-stretched film and the stretched film. In the laminate of the present invention, it is preferable that the base layer included in the non-stretched film is adjacent to the stretched film or is in contact with the stretched film via an adhesive layer.
[0057] <Stretched film> The film constituting the stretched film may be any known film depending on the application, and specific examples thereof include films made of polyesters such as polyethylene terephthalate and polyethylene naphthalate, polyethylene carbonate films, polyamide films made of nylon 6 and nylon 66, ethylene-vinyl alcohol copolymer films, polyvinylidene chloride films, and films made of polyolefins such as polypropylene. The stretched film made of the above-mentioned film may be used alone or in combination of two or more kinds. The above-mentioned film may be a film on which an inorganic substance such as aluminum, zinc, silica, or an oxide thereof is vapor-deposited.
[0058] Among them, at least one selected from the group consisting of a stretched PET film obtained by stretching a film formed from polyethylene terephthalate (PET) and a stretched PP film obtained by stretching a film formed from polypropylene (PP) is preferred. As the stretching method, a known method for producing a stretched film can be used. Specific examples include roll stretching, tenter stretching, and tubular stretching. The stretching ratio is usually 1.5 to 20 times, and preferably 2 to 15 times.
[0059] The thickness of the stretched film is usually 10 to 50 μm, preferably 15 to 45 μm, and when there are multiple stretched films, it is preferable that the thickness of each stretched film is within the above range. The total thickness of the laminate of the present invention is usually 30 to 150 μm, preferably 40 to 115 μm.
[0060] The laminate of the present invention has excellent low-temperature sealability and sufficient heat seal strength. The heat seal strength is the peel strength (N / mm) measured when two identical laminates are stacked with the sealant layer faces facing each other, the lower seal bar is heated at 70°C, the upper seal bar is heated at 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, the seal bar is heated at a pressure of 0.2 MPa for 1 second with a width of 5 mm, and then cooled, and a 15 mm wide test piece is cut from each heat-sealed test piece, and the heat-sealed portion of each test piece is peeled off in the direction of 180° to the laminate face at a crosshead speed of 300 mm / min.
[0061] The term "excellent low-temperature sealability" means that the maximum value of the heat seal strength of the laminate in the temperature range of 70°C to 120°C, i.e., the maximum value among the peel strengths of each test piece prepared by changing the temperature of the upper seal bar within the range of 70 to 120°C in the above-mentioned heat seal strength measurement, is 8N / 15mm or more, preferably 9N / 15mm or more, more preferably 10N / 15mm or more. The upper limit of the maximum value of the heat seal strength in the temperature range of 70°C to 120°C is usually 50N / 15mm. When the maximum value of the heat seal strength of the laminate in the temperature range of 70°C to 120°C is 8N / 15mm or more, heat sealing at low temperatures is possible and high-speed filling can also be accommodated.
[0062] Having sufficient heat seal strength means that the maximum value of the heat seal strength of the laminate in the temperature range of 70°C to 200°C, that is, the maximum value among the heat seal strengths of each test piece prepared by changing the temperature of the upper seal bar within the range of 70 to 200°C in the above-mentioned heat seal strength measurement, is preferably 15N / 15mm or more, more preferably 20N / 15mm or more, even more preferably 25N / 15mm or more, and particularly preferably 30N / 15mm or more. The upper limit of the maximum value of the heat seal strength in the temperature range of 70°C to 200°C is usually 100N / 15mm. If the maximum value of the heat seal strength of the laminate in the temperature range of 70°C to 200°C is 15N / 15mm or more, the adhesion of the sealed part is excellent and filling of heavy objects is also possible.
[0063] Here, in the above-mentioned heat seal strength measurement, the heat seal portion of the two sealed laminates peels off in the form of edge tearing, cohesive peeling, etc., or the film is torn, torn, etc. In the present invention, when the heat seal strength is first measured at a temperature range of 70° C. to 200° C., that is, among the test pieces having a heat seal strength of 30 N / 15 mm or more in the above-mentioned heat seal strength measurement, the heat seal portion of the laminate preferably peels off in the form of edge tearing in the form of peeling in the form of edge tearing in the test piece having the lowest temperature of the upper seal bar when the test piece was prepared.
[0064] The laminate of the present invention may also have excellent blocking resistance. The smaller the blocking force, the better the anti-blocking properties, and the blocking force is usually 15 N / m or less, preferably 10 N / m or less, and more preferably 8 N / m or less. If the blocking force is within the above range, blocking during storage can be effectively prevented. The method for measuring the blocking force will be described in detail in the Examples.
[0065] The laminate of the present invention may be produced by laminating a non-stretched film and a stretched film by dry lamination, non-solvent lamination, sand lamination, etc., or may be produced by laminating a non-stretched film and a stretched film by melt extrusion lamination. Among them, the lamination method by dry lamination or melt extrusion lamination is preferable.
[0066] The laminate of the present invention may further include at least one functional layer selected from a printed layer, a barrier layer, and an embossed layer to impart specific functions to the sealant layer, the substrate layer, and the stretched film. From the viewpoint of imparting functions to the sealant layer, the substrate layer, and the stretched film, it is preferable that the functional layer is adjacent to at least one layer or film selected from the sealant layer, the substrate layer, and the stretched film, or is in contact with the at least one layer or film selected from the sealant layer, the substrate layer, and the stretched film via an adhesive layer.
[0067] The above machine Energy layer For the cover, a resin film on which an inorganic compound or an inorganic oxide is vapor-deposited, a metal foil, a coating film of a resin having a special function, a resin film on which a pattern is printed, etc. can be used. The resin film used here may be the same as the resin film used for the base film, and further may be , Pu Plastic compounding agents and additives can also be added in any amount depending on the purpose, as long as they do not adversely affect other performance properties.
[0068] The resin film can be produced, for example, by a conventional film-forming method such as extrusion, cast molding, T-die, cutting, or inflation using one or more resins selected from the same group of resins as those for the base film, or by a multilayer co-extrusion film-forming method using two or more resins. Furthermore, from the viewpoint of film strength, dimensional stability, and heat resistance, the film can be stretched uniaxially or biaxially using, for example, a tenter system or a tubular system.
[0069] For example, a laminate further including a barrier layer can be produced by a method similar to the method for producing a laminate including a step of forming the barrier layer as the sealant layer, the base material layer, or a layer in the stretched film by metal deposition, a coating method, or a coextrusion method, and a step of laminating the non-stretched film and the stretched film described above. As described above, the laminate of the present invention has excellent low-temperature sealability and high heat seal strength. Furthermore, it also tends to have excellent blocking resistance and peeling appearance of the heat-sealed portion.
[0070] <Package> A package can be obtained from the laminate of the present invention. The package formed from the laminate of the present invention has excellent low-temperature sealability. Furthermore, the package formed from the laminate of the present invention thus obtained can maintain a heat seal strength equal to or greater than that of conventional products when molded at a conventional heat seal temperature (e.g., from 100°C to 160°C).
[0071] For example, a package can be produced by placing the sealant layers of the laminates face each other, or placing the sealant layer of the laminate face another film, and then heat-sealing at least a portion of the periphery from the outer surface side to form a desired container shape. Also, a sealed package can be produced by heat-sealing the entire periphery. If the forming process of this package is combined with a filling process of the contents, that is, the bottom and sides of the package are heat-sealed, the contents are filled, and then the top is heat-sealed, a package containing the contents can be produced. This package can be used in an automatic packaging device for solids such as snacks and bread, powders, or liquid materials.
[0072] Furthermore, the laminate or a sheet of the laminate can be used to fill a container, such as a container previously molded into a cup shape by vacuum forming, compressed air forming, or the like, a container obtained by injection molding, or a container formed from a paper base material, with the contents, and then the laminate of the present invention can be used as a lid to cover the container and heat seal the top or sides of the container to obtain a container packed with the contents. This container is suitable for packaging instant noodles, miso paste, jelly, pudding, snacks, etc.
[0073] When the laminate or packaging body has a mono-material structure, it can be effectively used as a recycled product. A molded product that is a recycled product of the laminate or packaging body can reduce the amount of newly polymerized plastic used, and can contribute to reducing the environmental load. EXAMPLES
[0074] Next, the laminate of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these. The materials used in the examples and comparative examples are shown below.
[0075] (A) Propylene-based polymer rPP (A-1): Random polypropylene (MFR (230°C, 2.16 kg load, compliant with ASTM D1238): 7 g / 10 min, melting point: 138°C, propylene content: 95 mol%, ethylene content: 2 mol%, 1-butene content: 3 mol%)
[0076] (B) 1-butene-α-olefin copolymer BPR (B-1): 1-butene-propylene copolymer (MFR (230°C, 2.16 kg load, conforming to ASTM D1238): 9 g / 10 min, MFR (190°C, 2.16 kg load, conforming to ASTM D1238): 4 g / 10 min, melting point: 100°C, 1-butene content: 87 mol%, propylene content: 13 mol%)
[0077] (C) Propylene-α-olefin copolymer PBR (C2-1): Propylene-1-butene copolymer (MFR (230°C, 2.16 kg load, conforming to ASTM D1238): 7 g / 10 min, MFR (190°C, 2.16 kg load, conforming to ASTM D1238): 3 g / 10 min, melting point: 75°C, propylene content: 74 mol%, 1-butene content: 26 mol%) PER (C1-1): Propylene-ethylene copolymer (MFR (230°C, 2.16 kg load, conforming to ASTM D1238): 8 g / 10 min, MFR (190°C, 2.16 kg load, conforming to ASTM D1238): 3.7 g / 10 min, melting point: 75°C, propylene content: 87 mol%, ethylene content: 13 mol%)
[0078] The melting point, heat seal strength and blocking strength of each (co)polymer were measured by the following methods.
[0079] [Melt point measurement method] (Propylene polymer) Using a differential scanning calorimeter (DSCPyris1 manufactured by PerkinElmer) in a nitrogen atmosphere (20 mL / min), about 5 mg of a sample was heated to 200°C and held for 10 minutes, then cooled to 30°C at 10°C / min and held for 5 minutes, and then heated to 200°C at 10°C / min. The temperature at the apex of the crystalline melting peak was determined as the melting point (Tm) of the propylene polymer.
[0080] (1-butene-α-olefin copolymer and propylene-α-olefin copolymer) Using a differential scanning calorimeter (Seiko Instruments DSC) in a nitrogen atmosphere (20 mL / min), about 10 mg of the sample was packed into a measurement aluminum pan, heated to 200°C at 100°C / min and held for 5 minutes, then cooled to -100°C at 10°C / min and heated to 200°C at 10°C / min. The temperature at the apex of the crystal melting peak at this time was taken as the melting point (Tm) of the 1-butene·α-olefin copolymer or propylene·α-olefin copolymer.
[0081] [Method of measuring heat seal strength] The sealant layer surfaces of the two laminates were placed together, and the lower seal bar was heated at 70°C, and the upper seal bar was heated at 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, with a pressure of 0.2 MPa for 1 second at a seal bar width of 5 mm, and then allowed to cool. Next, 15 mm wide test pieces were cut from each of the heat-sealed test pieces, and the peel strength was measured for each test piece when the heat-sealed portion was peeled off in the 180° direction with respect to the laminate surface at a crosshead speed of 300 mm / min, and the value was taken as the heat seal strength.
[0082] The heat seal strength was not measured for test pieces in which the temperature of the upper seal bar during the manufacture of the test piece when the heat seal strength first showed 30N / 15mm or more was higher than the temperature of the upper seal bar during the manufacture of the test piece in which edge cuts or cohesive peeling occurred in the evaluation of peel appearance described below. In addition, the upper limit of the temperature of the upper seal bar in this test was set to 180°C, and for test pieces in which the heat seal strength did not exceed 30N / 15mm up to 180°C, the heat seal strength was not measured at subsequent temperatures.
[0083] (Low temperature sealing) The low-temperature sealability of the laminate was evaluated according to the following criteria. ○: The maximum heat seal strength in the temperature range of 70℃ to 120℃ is 8N / 15mm or more. ×: The maximum heat seal strength in the temperature range of 70℃ to 120℃ is less than 8N / 15mm
[0084] (Maximum heat seal strength) The maximum heat seal strength of the laminate was evaluated according to the following criteria. ○: The maximum heat seal strength in the temperature range of 70℃ to 200℃ is 30N / 15mm or more. ×: The maximum heat seal strength in the temperature range of 70℃ to 200℃ is less than 30N / 15mm
[0085] (Peeled appearance (peeled form)) In the above heat seal strength measurement, the peeling state of the heat seal part of the sample where the heat seal strength was 30 N / 15 mm or more was peeled was confirmed, and the occurrence of edge cut, cohesive peeling, film cut, and film tearing was evaluated according to the following criteria. In the above heat seal strength measurement, if the heat seal strength did not exceed 30 N / 15 mm up to 180°C, the peeling appearance at the maximum value was evaluated. ○: The edge of the welded surface was broken (edge breakage) △: Coagulation and peeling occurred ×: The film was cut or torn.
[0086] [Method of measuring blocking force] The laminate was cut into strips 200 mm wide, two strips of laminate were placed together with the sealant side facing each other, and placed in an air oven at 50°C, with a load of 20 kg applied from above the stacked laminate, and cured for three days.The laminate was then removed from the air oven, and the strength was measured when the two strips of laminate were peeled off in a direction 180° from the laminate surface at a speed of 200 mm / min, and this value was taken as the blocking force.
[0087] (Blocking force) The blocking strength of the laminate was evaluated according to the following criteria. ○: Blocking force is less than 10N / m △: Blocking force is 10N / m or more
[0088] [Example 1] A resin composition for producing a sealant layer was prepared by blending 60 parts by mass of rPP (A-1), 30 parts by mass of BPR (B-1), and 10 parts by mass of BPR (C2-1). Furthermore, 1000 ppm of erucic acid amide as a slip agent and 1200 ppm of silica (particle size 3 μm) as an antiblocking agent were added and blended into the resin composition.
[0089] Using two extruders connected to a T-die, the resin composition for producing the sealant layer to which the additives were added and rPP (A-1) for producing the base layer were fed to each extruder, the die and resin temperatures were set to 230°C, and the extrusion amount of each extruder was adjusted to produce an unstretched film in which a 50 μm-thick unstretched base layer and a 20 μm-thick unstretched sealant layer were laminated by co-extrusion molding. Next, a 25 μm-thick stretched PET film (manufactured by Toray) was laminated on the base layer surface of the obtained unstretched film via an adhesive layer by dry lamination to produce a laminate. Using this laminate, the low-temperature sealability, maximum heat seal strength, peeling appearance, and blocking force were measured by the above-mentioned measurement methods. The results are shown in Table 1.
[0090] [Examples 2 to 12, Comparative Examples 1 to 4] Laminates were produced in the same manner as in Example 1, except that the composition of the resin composition for producing the sealant layer was changed to the composition shown in Table 1, or a stretched PP film (manufactured by Mitsui Chemicals Tohcello) was used as the stretched film. Using each of these laminates, low-temperature sealability, maximum heat seal strength, peel appearance, and blocking force were measured by the above-mentioned measuring methods. The results are shown in Table 1.
[0091] [Table 1]
Claims
1. 20 to 75% by mass of a propylene-based polymer (A); 20 to 75% by mass of a 1-butene / α-olefin copolymer (B); Propylene / α-olefin copolymer (C) 5 to 40 mass % a sealant layer made of a resin composition comprising the following: (wherein the total of the propylene-based polymer (A), the copolymer (B) and the copolymer (C) is 100 mass%); and Base material layer is an unstretched film having: The content of the copolymer (B) is equal to or greater than the content of the copolymer (C); The total content of the copolymer (B) and the copolymer (C) is 25 to 80 mass %, The propylene polymer (A) has a melting point measured by differential scanning calorimetry of 120° C. or more and 170° C. or less; The copolymer (B) has a melting point of less than 120° C. as measured by differential scanning calorimetry or no melting point is observed by differential scanning calorimetry, contains 51 to 99 mol % of structural units derived from 1-butene, and contains 1 to 49 mol % of structural units derived from an α-olefin having 2 to 3 carbon atoms or 5 to 20 carbon atoms (with the proviso that the total of the structural units derived from 1-butene and the structural units derived from the α-olefin is 100 mol %); The copolymer (C) has a melting point of less than 120° C. as measured by differential scanning calorimetry, or no melting point is observed as measured by differential scanning calorimetry, and contains 51 to 95 mol % of structural units derived from propylene and 5 to 49 mol % of structural units derived from an α-olefin having 2 carbon atoms or 4 to 20 carbon atoms (however, the total of the structural units derived from propylene and the structural units derived from the α-olefin is 100 mol %). Unstretched film.
2. The non-oriented film according to claim 1, wherein the copolymer (C) comprises one or more propylene / α-olefin copolymers selected from the group consisting of propylene / ethylene copolymers (C1) and propylene / 1-butene copolymers (C2).
3. The non-oriented film according to claim 1, wherein the base layer contains the propylene-based polymer (A) (which may be the same as or different from the propylene-based polymer (A) contained in the sealant layer).
4. The non-oriented film according to claim 1, wherein the sealant layer has a thickness of 3 to 30 μm, and the base layer has a thickness of 10 to 100 μm.
5. A laminate comprising the unstretched film according to claim 1 and a stretched film.
6. 6. The laminate of claim 5, wherein the oriented film is a film selected from the group consisting of oriented polyethylene terephthalate films and oriented polypropylene films.
7. The laminate according to claim 5, wherein the stretched film has a thickness of 10 to 50 μm.
8. The maximum heat seal strength in the temperature range of 70° C. or more and 120° C. or less is 8 N / 15 mm or more, The maximum heat seal strength in the temperature range of 70° C. or more and 200° C. or less is 15 N / 15 mm or more, 6. The laminate according to claim 5, wherein when a heat seal strength measurement is performed in a temperature range of 70°C to 200°C, the peeling mode of the heat seal portion is edge tearing when the heat seal strength is 30 N / 15 mm or more.
9. Further comprising at least one functional layer selected from a printing layer, a barrier layer, and an embossed layer; The laminate according to claim 5 , wherein the functional layer is adjacent to or in contact with at least one layer or film selected from the sealant layer, the substrate layer, and the stretched film via an adhesive layer.
10. A packaging material formed from the laminate according to any one of claims 5 to 9.
Citation Information
Patent Citations
Resin composition for sealant film, and sealant film
JP1999221884A
1-butene ethylene copolymer
JP2017002315A
Laminate
JP2020192695A
Laminate
JP2020192696A
Stretched film and use therefor
JP2021063162A